THE CALCIUM BINDING SITES OF THE BAKERS' YEAST TRANSKETOLASE (Journal of Sciences, Islamic Republic of Iran)
The calcium binding sites of Bakers' Yeast Transketolase (TK) was elucidated by estimating the pKa values of the functional groups that bind to calcium. These pKa's were found to be 6.25 and 7.2 relating to the pKa's of the two immidazol moieties of histidine residues on the enzyme. The rate of the binding of calcium to the enzyme was obtained separately as a function of pH. Maximum values were obtained at the pKa's of the immidazol rings of histidine correlating closely with the values obtained by direct titration. The activity rate studies as a function of pH showed that the enzyme, when bound to its cofactors, becomes further activated over and above the regular increasing trend of the pH rate profile at similar pH's which are optimal for calcium binding